The relationship between literary criticism and journalism (Eurasian Journal of Philology Science and Education, 2020)
The article deals with the formation and development of literary criticism and is based on its growingin the press. The analysis of materials in Kazakh newspapers and magazines of the late XIX – early XXcenturies shows the evolution of the formation of the Kazakh literary criticism. The genre types and formsof the first critical articles are classified on the basis of publications. The difference between journalisticcriticism and literary criticism in newspaper and magazine context is also distinguished. Although theliterary nature of literary criticism and Kazakh literary criticism have always been not only the recognition of literature, but also the self-actualization of society. It can be concluded that literary critics areoften considered by literature and art as a means of true recognition.The article analyzes the content ofa number of literary magazines-Newspapers that appeared after the 90s of the XX century, starting fromthe 20s of the XX century.New judgments and research were given on the role of literary Newspapersand magazines in the history of literature.The purpose of the article is to determine the place of literaryNewspapers and magazines in the history of literature and the relationship of criticism to the field ofjournalism.